Ending PJ paralysis for hospitalised patients: a quality improvement initiative - Frances Carr; Pamela Mathura; Jennifer Symon (BMJ Open Quality)
Introduction PJ paralysis refers to the negative effects experienced by hospitalised patients who remain inactive and dressed in hospital clothing, and is a serious problem, affecting one-third of hospitalised older adults. This study evaluated the impact of a multicomponent hospital-based intervention to get patients out of bed, dressed in non-hospital attire, and moving around/mobilised.Methods A 3-month quality improvement initiative was conducted at one hospital unit in Western Canada, which aimed for 50% of all patients to be dressed in their own clothing by midday, sitting up in a chair for all meals and mobilising to activities. Healthcare providers, patients and family members received PJ paralysis education, and a new patient dress code care standard and physician patient care order were implemented. Measures included: daily percentage of patients dressed and up for meals, weekly mobilisation rates, patient and provider satisfaction, and complication rates. Descriptive statistics were completed.Results From July to October 2019, 70 patients participated. Approximately 14.3% of patients were dressed in their own clothing daily, 6.4% were sitting for all three meals, and the weekly mean number of patients mobilising to activities was 0.9 (SD 0.7) and mobilising for other reasons was 4.5 (SD 1.3). Five physician care orders were written. A trend was observed towards decreased falls, with minimal change in the number of staff, nursing assessment time and complication rates. Patient feedback revealed improvement in their self-identity.Conclusion Alleviating PJ paralysis in hospitalised older patients requires a complex multifactorial approach. Despite not achieving the project aim, the intervention demonstrated positive impacts without complications or additional workload, and ease of implementation suggests feasibility and (potential) long-term sustainability. Further research is needed to explore the experiences and perceptions of patients and healthcare providers to identify facilitators and barriers, which may aid in enhancing and implementing future interventions.